Dissemination of Citation Writing Principles and Techniques in Scientific Article Manuscripts - Janes Sinaga; Juita Sinambela (Peneliti Teknologi Teknik Indonesia, 2023)
The purpose of this community service is for each writer to understand the principles and techniques of writing citations in scientific article manuscripts. Academic scientific articles are academic essays that use scientific principles presented scientifically and in scientific language. Making scientific publications is an activity that requires precision, including looking for references. In writing scientific articles, citations are very necessary and very useful, especially in matters relating to new topics that can support research results arguments. This research uses qualitative methods through literature review. In making scientific papers it is very important to include citations on each quote taken from the previous author. This is done so that quotes or references are used to enhance the work of other authors or to cite to credit individual work.